2009
DOI: 10.1002/per.733
|View full text |Cite
|
Sign up to set email alerts
|

More than the Big Five: Egoism and the HEXACO model of personality

Abstract: Egoism is a personality trait that is associated with self‐enriching and self‐centred behaviours. Research has suggested that egoism lies beyond the Big Five personality factors. Recently, the HEXACO model of personality has been proposed as an alternative to the Big Five model. In three studies, the relation between the HEXACO Personality Inventory and egoism, conceptualized using three different questionnaires (DPQ Egoism, SPI Egotism and the Egoism Scale), is investigated. In all three studies, the HEXACO H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 29 publications
2
43
0
2
Order By: Relevance
“…r ¼ .82, see e.g. De Vries, De Vries, De Hoogh, et al, 2009). Abovementioned findings suggest that there is not much evidence for strong conceptual overlap between Conscientiousness and Honesty-Humility.…”
Section: Honesty-humility and Academic Criteriamentioning
confidence: 94%
“…r ¼ .82, see e.g. De Vries, De Vries, De Hoogh, et al, 2009). Abovementioned findings suggest that there is not much evidence for strong conceptual overlap between Conscientiousness and Honesty-Humility.…”
Section: Honesty-humility and Academic Criteriamentioning
confidence: 94%
“…Lee, Ogunfowora, & Ashton, 2005;Ashton & Lee, 2009;de Vries, de Vries, de Hoogh, & Feij, 2009). Also, significant differences are expected in the Honesty-Humility scale, where women should score higher Ashton & Lee, 2009;de Vries et al, 2009). Previous studies did not provide consistent findings for gender differences in Openness to Experience, Agreeableness and Conscientiousness.…”
mentioning
confidence: 86%
“…A greater gender difference is expected in the Emotionality dimension, suggesting that women are more emotional than men (e.g. Lee, Ogunfowora, & Ashton, 2005;Ashton & Lee, 2009;de Vries, de Vries, de Hoogh, & Feij, 2009). Also, significant differences are expected in the Honesty-Humility scale, where women should score higher Ashton & Lee, 2009;de Vries et al, 2009).…”
mentioning
confidence: 96%
“…Generally speaking, Honesty-Humility has been defined as ''the tendency to be fair and genuine in dealing with others'' (Ashton & Lee, 2007, p. 156), thus representing people's willingness to refrain from exploiting others or bending rules and norms -even if such actions would be individually beneficial and bear little risk of retaliation or sanctions (Hilbig & Zettler, 2009). Indeed, various studies have demonstrated that this sixth basic factor accounts for variance in socially desirable outcomes and behavior -often beyond the influence of the remaining five factors within the HEXACO model and/or the classic Big Five (De Vries, De Vries, De Hoogh, & Feij, 2009;Lee, Ogunfowora, & Ashton, 2005). Specifically, Honesty-Humility has been associated with more prosocial behavior and cooperativeness (Hilbig, Glöckner, & Zettler, 2014;Hilbig, Thielmann, Hepp, Klein, & Zettler, 2015;, less socio-sexuality and fewer sexual quid pro quos (Ashton & Lee, 2008b;Lee et al, 2013), more moral behavior and honest responding (Hilbig, Moshagen, & Zettler, 2015) as well as higher integrity, less counterproductive work behavior, and other related criteria (Lee, Ashton, & De Vries, 2005;Marcus, Lee, & Ashton, 2007;Zettler & Hilbig, 2010).…”
Section: Honesty-humility and Dishonest Behaviormentioning
confidence: 99%